Exercise improved age-associated changes in the carotid blood velocity waveforms - Noor Azmi, Azran Azhim; M. , Katai; M., Akutagawa; Y., Hirao; K., Yoshizaki; S., Obara; M. , Nomura; H., Tanaka; H., Yamaguchi; Y., Kinouchi (Biomedical & Pharmaceutical Engineering Cluster, Nanyang Technological University, 2007)
Physiological blood flow velocity in common carotid artery (CCA) is altered markedly with advancing age. It is unknown that regular aerobic exercise is able to improve blood flow velocity waveforms in either healthy young or healthy older individuals. We investigate the role of regular exercise on the age-associated alterations in blood velocity waveforms in CCA by using cross-sectional and intervention approaches. First, we study 91 putatively healthy volunteers with age range of 20-76 years: 65 subjects are sedentary and 26 subjects are regular exercisetrained. We assess the blood velocities at rest in peak systolic (S1), second systolic (S2), incisura between systole (I) and peak diastolic (D), and end-diastolic (d) in young, middle-aged and older subjects. Blood velocities in S1 are higher in exercise-trained, whereas S2, D and d are not different between trained and sedentary individuals. However, the indices of S1/S2 and D/I have marked higher values in exercise-trained adults. Second, we study 7 young sedentary healthy subjects before and after 1-month aerobic exercise intervention. The aerobic exercise increases whole velocity waveforms in CCA with association of decreased heart rate. In conclusion, regular exercise improves age-associated decrease in blood flow velocities in the healthy young, middle-aged and older individuals and restores levels after 1-month exercise in previously sedentary young men.